2019
DOI: 10.1017/s0950268818003424
|View full text |Cite
|
Sign up to set email alerts
|

School sessions are correlated with seasonal outbreaks of medically attended respiratory infections: electronic health record time series analysis, Wisconsin 2004–2011

Abstract: Increased social contact within school settings is thought to be an important factor in seasonal outbreaks of acute respiratory infection (ARI). To better understand the degree of impact, we analysed electronic health records and compared risks of respiratory infections within communities while schools were in session and out-of-session. A time series analysis of weekly respiratory infection diagnoses from 28 family medicine clinics in Wisconsin showed that people under the age of 65 experienced an increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Studies have demonstrated an increased frequency of illness in association with school attendance. [12][13][14] Any going out at night, gathering and socialising was prevented during lockdown. Additionally, increased hygiene practices such as handwashing could be expected to reduce the frequency of community-acquired illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated an increased frequency of illness in association with school attendance. [12][13][14] Any going out at night, gathering and socialising was prevented during lockdown. Additionally, increased hygiene practices such as handwashing could be expected to reduce the frequency of community-acquired illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…7 , 8 Even though influenza transmission among school‐aged children frequently precedes subsequent community transmission, 9 , 10 there have been no systematical evaluations of school‐based monitoring of influenza activity for complementing routine surveillance or serving as an early‐warning system for increased influenza activity in the wider community. Monitoring school absenteeism is feasible, as seasonal outbreaks occur between late fall and mid‐spring while schools are in session, 11 , 12 and most of the 13,588 school districts 13 across the United States collect daily absenteeism data using electronic school information systems. 14…”
Section: Introductionmentioning
confidence: 99%
“…We accounted for this through examinations of seasonal signatures for Winter and Spring Break holiday effects though not elsewhere within our analyses. A simple approach of comparing risks of respiratory infections within communities while schools were in session and out-of-session is a viable approach to start [40], yet the complexity of accounting for overlapping events and delayed effects is daunting.…”
Section: Discussionmentioning
confidence: 99%